Symposium 1: Learning, Teaching and Assessment in Networked Learning - Hodgson, Vivien; Reynolds, Michael (Proceedings of the International Conference on Networked Learning, 2010)
The focus of our paper is on Theme 2 of the Networked Learning Manifesto which focused on Learning Teaching and Assessment and stated as follows: Networked e-learning as envisaged in this manifesto requires models of learning that are based on participation and not ones that are based on transmission. This requires as much emphasis on learning processes and learning to learn as on subject knowledge. Educational values which contribute to quality in learning and teaching environments are those that seek to encourage dialogue, exchange of ideas, intrinsic approaches to study and engagement. It is this that we need to support through networked e-learning. Networked e-learning provides the opportunity for developing innovative assessment practices in which teachers and learners collaborate in the assessment process. Networked e-learning is not a depersonalising experience. The careful integration of course design and innovative assessment can create as intimate an educational experience as a face-to-face encounter. In this paper we look at these statements in more detail in terms of what the ideas behind each of them were and the meaning and relevance of some of the key ideas to the current theory and practice of networked learning. Our approach is to review current thinking sufficiently to highlight issues which the manifesto raises and in addition, to examine these issues from the perspective of an empirical research study of networked learning practice. We have summarised key issues in the final section of the paper as questions which we hope might provide criteria for evaluating how the principles incorporated in the manifesto are reflected in current networked learning theory and in practice. The questions we suggest are: What values and beliefs underlie practice? Are claims to democratic pedagogy justified? What interpretations of ‘community’ are found in use? Do they take account of the social and political processes involved? As tutors, what ideas do we draw on to help make sense of these processes? Do Networked Learning practices support critical reflection and the co-construction of knowledge? Do assessment procedures reflect the same values as are embodied in other aspects of the pedagogy? If there are differences, are they at least acknowledged? Do our pedagogies support space and time for trust and confidence to develop?